The process of globalization of Éducation and its effect in context in the French-speaking Africa: case of the Central African Republic - (:unkn) unknown (My University, 2011)
This research deals with issues related to the globalization process of Éducation and its effectsin context in sub-Saharan french-speaking countries of Africa in general, by analyzing andtaking support on the situation of the Central African Republic, as a sample of this Africa.This process of globalization affects all areas of society today and is part of a movement thatexports practices and models from North to South. Modern Éducation does therefore notescape this movement. Globalization calls African national Éducational systems to atransformation and to adoption of a supranational school model. But this model is largelyabove the national, local and specific realities. The Éducation For All (EFA) program, led outby the international community through the supranational instances (Unesco, Unicef, WorldBank and Monetary Fund International etc.) puts forward the problem in terms of national andlocal anchor in the general policy of each State-nation. The likely failure of theimplementation of this program is to impute to a policy which is above the realities of Africancountries and the Third-World in general.
Keywords: African Research